Implementasi Teknologi pada Pariwisata Budaya di Madura - Iqbal, Fikri Dainuri; Arief, Mohammad (Universitas Trunojoyo Madura, 2025)
This study aims to determine the role of marine tourism destinations with rokat tase cultural attractions and adopt technology to increase tourist visits and find out the meaning in the culture in Tengket village, Arosbaya District, Bangkalan Regency. This research was carried out qualitatively, using ethnographic studies, data collection techniques using interview, observation and documentation techniques, data analysis techniques using data collection, data reduction, data presentation and conclusions along with verification. The results of this study show the role of marine tourism destinations with rokat tase cultural attractions' to increase tourist visits, better management, dare to take risks in development, receive directions and suggestions from community leaders and all relevant stakeholders in an effort to improve the quality of marine tourism destination managers with rokat tase cultural attractions. This can improve services to the maximum which will bring good influence to marine tourism destinations in Arosbaya district.